1986
DOI: 10.1002/eqe.4290140505
|View full text |Cite
|
Sign up to set email alerts
|

Damping in tall buildings—a mechanism and a predictor

Abstract: SUMMARYOnly when the data base is of sufficient quality can a theoretical model of any process be justified. Such a data base has recently been assembled in the field of damping in tall buildings. It is now possible to specify a damping value appropriate to a particular building vibrating at a specified amplitude which is well correlated with values which are measured in practice. The mechanism on which this predictor is based suggests that the predictor will be applicable to other types of structure as well. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(77 citation statements)
references
References 13 publications
3
74
0
Order By: Relevance
“…Another contributing factor may be that the in situ compressive strengths are higher than those assumed in design, resulting again in a stiffer structure. Meanwhile, despite the signifi cant uncertainty surrounding damping prediction, the observed damping values from the PSD, essentially under ambient vibrations, are quite consistent with the 1·5% value assumed in the design, especially considering that damping levels are generally hypothesized to increase with amplitude (Jeary, 1986). These analyses were twice repeated on different cross-sections of the dataset and showed remarkable consistency with the values reported in Table 1 (Abdelrazaq et al, 2005;Pirnia et al, 2007).…”
Section: The Role Of Amplitude Dependencesupporting
confidence: 74%
See 1 more Smart Citation
“…Another contributing factor may be that the in situ compressive strengths are higher than those assumed in design, resulting again in a stiffer structure. Meanwhile, despite the signifi cant uncertainty surrounding damping prediction, the observed damping values from the PSD, essentially under ambient vibrations, are quite consistent with the 1·5% value assumed in the design, especially considering that damping levels are generally hypothesized to increase with amplitude (Jeary, 1986). These analyses were twice repeated on different cross-sections of the dataset and showed remarkable consistency with the values reported in Table 1 (Abdelrazaq et al, 2005;Pirnia et al, 2007).…”
Section: The Role Of Amplitude Dependencesupporting
confidence: 74%
“…This situation is unfortunate since, of all the dynamic properties that can be modifi ed, increases in damping are the only ones that have consistently proven to reduce accelerations. Although there have been some efforts to develop empirical predictive tools for damping estimation based on full-scale observations (Jeary, 1986;Satake et al, 2003), there is still signifi cant scatter in the data, as well as limited information for high-rise buildings, which tend to be the most sensitive to acceleration-based perception criteria. This scatter is in part due to the relatively minor participation of damping in overall structural response.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, from field measurements made over the last three decades, it has been recognized that natural frequencies and damping ratios are nonlinear parameters and may increase with vibration amplitude [13][14][15]. However, in structural design, natural frequencies and damping ratios are usually assumed to be constant and independent of structural response magnitudes, and the limited number of studies of dynamic response analysis of buildings considering amplitude-dependent dynamic characteristics has shown that the current design assumption does not appear to be conservative [16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, since there is no means to estimate damping effectively in the design stage, the earliest full-scale efforts were directed towards short-term monitoring of suites of buildings to develop damping databases (Davenport and Hill-Carroll, 1986;Jeary, 1986;Lagomarsino, 1993). Since then, monitoring efforts have grown increasingly long-term (Brownjohn et al, 1998;Li et al, 1998;Kijewski-Correa et al, 2006) with the objective of observing the structure under a range of wind events to validate the design process more systematically, especially in extreme events such as typhoons (Li et al, 2005;Xu and Zhan, 2001).…”
Section: Introductionmentioning
confidence: 99%